2023
DOI: 10.1021/jacs.3c06738
|View full text |Cite
|
Sign up to set email alerts
|

Operando Mössbauer Spectroscopic Tracking the Metastable State of Atomically Dispersed Tin in Copper Oxide for Selective CO2 Electroreduction

Ruru Chen,
Jian Zhao,
Yifan Li
et al.

Abstract: Metastable state is the most active catalyst state that dictates the overall catalytic performance and rules of catalytic behaviors; however, identification and stabilization of the metastable state of catalyst are still highly challenging due to the continuous evolution of catalytic sites during the reaction process. In this work, operando 119Sn Mössbauer measurements and theoretical simulations were performed to track and identify the metastable state of single-atom Sn in copper oxide (Sn1–CuO) for highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In electrolysis, complicated factors, including the electrolyte and pH, determine the surface states of electrocatalysts, where various reactions occur for targeted products [2a,9c] . However, the simple catalyst model in most cases leads to the intrinsic defect of deviating from the realistic reaction surface, particularly in varied solution environments.…”
Section: Resultsmentioning
confidence: 99%
“…In electrolysis, complicated factors, including the electrolyte and pH, determine the surface states of electrocatalysts, where various reactions occur for targeted products [2a,9c] . However, the simple catalyst model in most cases leads to the intrinsic defect of deviating from the realistic reaction surface, particularly in varied solution environments.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S9 (Supporting Information), after the electrochemical reduction at −0.6 versus RHE for 10 mins, Raman peaks at 286.7 and 465.3 cm −1 for CuO and Cu 2 O disappear, indicating that the CuO NWs has been completely reduced to metallic Cu. [12,37] Therefore, the electrochemical reduction at −0.6 versus RHE for 1 h is enough to completely reduce CuO to Cu NWs. Furthermore, we performed quasi in situ XPS according to literatures.…”
Section: Characterizations Of Electrocatalystsmentioning
confidence: 99%
“…129 (g) 119 Sn Mo ¨ssbauer spectroscopy as a probe technique to track the catalyst's metastable species. 130 environment of the single atomic sites. By fitting the results from EXAFS, important parameters such as bond length and coordination numbers can be inferred.…”
Section: Characterization Techniques Of Sacsmentioning
confidence: 99%
“…Chen et al reported a copper oxide-supported atomically dispersed Sn catalyst for the CO 2 RR. 130 In their study, they employed 119 Sn Mo ¨ssbauer spectroscopy as a probe technique to track the catalyst's metastable species. The Mo ¨ssbauer spectroscopy results revealed that the atomically dispersed Sn 4+ sites on the CuO substrate underwent a transformation from Sn 4+ -O 4 -Cu 2+ to a metastable state of Sn 4+ -O 3 -Cu + during the CO2RR (Fig.…”
Section: Characterization Techniques Of Sacsmentioning
confidence: 99%